2021
DOI: 10.1111/dom.14343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liraglutide versus sitagliptin on circulating cardiovascular biomarkers, including circulating progenitor cells, in individuals with type 2 diabetes and obesity: Analyses from the LYDIA trial

Abstract: The mechanisms behind the beneficial cardiovascular effects of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) compared with dipeptidyl peptidase‐4 inhibitors (DPP4is) remain largely unknown, despite both targeting the incretin pathway to improve glycaemic control. In these prespecified secondary analyses of the LYDIA trial, we examined the impact of the GLP‐1RA liraglutide (1.8 mg once‐daily) and the DPP4i sitagliptin (100 mg once‐daily) on circulating cardiovascular biomarkers associated with atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In addition, analysis of a 52-week phase 2 trial investigated once-daily ≤ 0.4 mg doses of s.c. semaglutide (N = 957) and the STEP phase 3 trials investigated s.c. semaglutide 2.4 mg dose in subjects with overweight and obesity with or without type 2 diabetes (total N = 4684); these trials identified consistent reductions in hsCRP with once-daily semaglutide ≤ 0.4 mg and once-weekly s.c. semaglutide 2.4 mg [ 28 32 ]. An analysis of subjects with type 2 diabetes and obesity in the LYDIA trial found there was no significant difference in the effects of liraglutide on hsCRP compared with the dipeptidyl peptidase-4 inhibitor sitagliptin [ 33 ]. However, a recent meta-analysis, which included data from 40 randomized controlled trials in subjects with type 2 diabetes, found significant improvements with GLP-1RAs compared with standard diabetes therapies (including sulfonylureas, insulins, dipeptidyl peptidase-4 inhibitors, thiazolidinediones) and placebo in several clinical biomarkers, including CRP, tumor necrosis factor-alpha, and adiponectin (markers of inflammation) and malondialdehyde (a marker of oxidative stress) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of a 52-week phase 2 trial investigated once-daily ≤ 0.4 mg doses of s.c. semaglutide (N = 957) and the STEP phase 3 trials investigated s.c. semaglutide 2.4 mg dose in subjects with overweight and obesity with or without type 2 diabetes (total N = 4684); these trials identified consistent reductions in hsCRP with once-daily semaglutide ≤ 0.4 mg and once-weekly s.c. semaglutide 2.4 mg [ 28 32 ]. An analysis of subjects with type 2 diabetes and obesity in the LYDIA trial found there was no significant difference in the effects of liraglutide on hsCRP compared with the dipeptidyl peptidase-4 inhibitor sitagliptin [ 33 ]. However, a recent meta-analysis, which included data from 40 randomized controlled trials in subjects with type 2 diabetes, found significant improvements with GLP-1RAs compared with standard diabetes therapies (including sulfonylureas, insulins, dipeptidyl peptidase-4 inhibitors, thiazolidinediones) and placebo in several clinical biomarkers, including CRP, tumor necrosis factor-alpha, and adiponectin (markers of inflammation) and malondialdehyde (a marker of oxidative stress) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in small placebo-controlled randomized controlled trials, the combination of metformin and liraglutide may reduce the levels of the most atherogenic LDL subfraction and C-reactive protein in patients with coronary artery disease and new onset type 2 diabetes [7]. Compared to sitagliptin, liraglutide was also found to increase VEGF, which is a mediator of angiogenesis and might attenuate the adverse consequences of large vessel atherosclerosis by inducing the formation of collateral vessels in obese type 2 diabetic patients [8]. As recently summarized by Ussher et al, GLP-1RA-mediated cardiovascular protection could be mainly attributed to their vascular anti-inflammatory and anti-atherosclerotic actions, alongside improvements in heart glucose metabolism, fibrosis, oxidative stress, cardiomyocytes viability, and, even though to a small extent, in blood pressure [9].…”
Section: Atherosclerosis and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…This finding suggests that a GLP-1 receptor agonist has beneficial effects on endothelial function by promoting brown adipocyte differentiation. However, the results of clinical studies regarding the effects of GLP-1 receptor agonists on endothelial function have been conflicting [ 174 , 175 , 176 , 177 ]. In addition, there is no information on the effects of semaglutide on endothelial function.…”
Section: Treatment Of Obesity For Improvement Of Endothelial Functionmentioning
confidence: 99%